FRI0205 ANTIMALARIAL AGENTS IMPROVE PHYSICAL FUNCTIONING IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Parodis, Ioannis; Soukka, Sofia; Gomez, Alvaro; Enman, Yvonne; Johansson, Petter; Emamikia, Sharzad; Chatzidionysiou, Katerina
Abstract : Background: Patients with systemic lupus erythematosus (SLE) suffer an impaired health-related quality of life (HRQoL), and the majority of them experience fatigue as a major problem. Traditionally, treatment of SLE has been symptomatic, and antimalarial agents (AMA) are considered a cornerstone of SLE treatment. In previous literature, results regarding the effect of antimalarial agents on HRQoL have been conflicting. Objectives: In this study, we aimed at investigating the potential influence of AMA on SLE patients' self-perception of HRQoL aspects. Methods: We utilised pooled baseline data from the BLISS-52 and BLISS-76 clinical trials of belimumab (n=1684). Access to data was granted by GlaxoSmithKline. The patients' HRQoL and fatigue were self-reported using the Medical Outcomes Study (MOS) short form 36 (SF-36) health survey, the functional assessment of chronic illness therapy (FACIT)-Fatigue scale and the three-level EuroQol- 5 Dimension (EQ-5D) questionnaire. Minimal clinically important difference (MCID) was set to ≥5.0 points for SF-36 subscales, ≥2.5 points for SF-36 component summary scores, and ≥4 points for FACIT-Fatigue scores. High disease activity was defined as a SELENA-SLEDAI score ≥10. Organ damage was assessed using the SLICC/ACR Damage Index (SDI). The non-parametric Mann-Whitney U test was used for comparisons between AMA users and non-users. Linear regression models were next used in order to adjust for possible confounding factors; these included age, sex, ethnic origin, SLE disease activity, SLE duration, organ damage, corticosteroid use and use of other immunosuppressive agents. Results: Results are presented as mean values ± standard devation. Patients receiving AMA (n=1098) performed better than patients who did not receive AMA (n=586) with regard to SF-36 physical component summary (PCS) scores (39.6 ± 9.5 versus 38.1 ± 9.9; P =0.001), physical functioning (61.1 ± 24.9 versus 55.0 ± 26.5; P <0.001), role physical (53.2 ± 26.9 versus 50.3 ± 27.7; P =0.036), bodily pain (49.5 ± 23.8 versus 47.1 ± 25.3; P =0.016), FACIT-Fatigue scores (30.5 ± 11.8 versus 29.3 ± 11.9; P =0.046), EQ-5D scores (0.75 ± 0.18 versus 0.72 ± 0.19; P =0.004) and EQ-5D visual analogue scale (VAS) scores (64.6 ± 19.4 versus 61.7 ± 18.6; P =0.001). The difference in SF-36 physical functioning was the greatest one among the SF-36 parameters, exceeding the corresponding MCID (≥5.0 points). The association between AMA use and better physical functioning was still significant after adjustment for potential confounding factors (standardised coefficient, β=0.08; P =0.001). In this analysis, Asian patients performed better in physical functioning (β=0.07; P =0.004) while African/African American patients performed worse (β=-0.07; P =0.003). High disease activity (β=-0.09; P <0.001) and organ damage (β=-0.12; P <0.001) were also independent factors of worse physical functioning, whereas corticosteroid use independently improved the outcome (β=0.06; P =0.022). Conclusion: AMA use contributes to better physical functioning in patients with SLE, independently of other factors. Acknowledgement: The authors would like to thank GlaxoSmithKline (Uxbridge, UK) for granting access to the data from the BLISS-52 and BLISS-76 trials (ClinicalTrials.gov identifiers NCT00424476 and NCT00410384, respectively) through the Clinical Study Data Request (CSDR) consortium. Disclosure of Interests: None declared